Der Prozess - Bopp, Dominik; Dalla Palma, Helin; Diethelm, Dominique; Geering, Florian; Hunkemöller, Pia; Kiritharan, Gishok; Kistler, Alexander; Liniger, Isabel; Lisik, Natalie; Nastovski, Nikola; Reusser, Christoph; Rudolph, Nancy; et al. (sui generis Verlag, 2024)
Processes play a central role in legal science. The XXIV edition of the APARIUZ series puts the court process in the foreground and at the same time opens our eyes to other legal processes. In addition to procedural issues, the authors deal with processes of social protection, transparency, internationalization and method development. The anthology includes contributions from young scientists at the University of Zurich as well as guest contributions from established personalities from science and practice.